An appraisal of the performance of two (2) Development Financial Institutions (DFIs) in Malaysia - Islam, Mohd Aminul (Management Journals, USA, 2012)
This paper aims to assess the financial performance of two (2) Development Financial Institutions (DFIs) in Malaysia namely; Bank Simpanan Nasional or National Savings Bank (BSN) and Bank Kerjasama Rakyat Malaysia or Cooperative Bank (BR) for a period of 5 years spanning from 2006 to 2010. The DFIs are specialized financial institutions established by the government to achieve the socio-economic development objectives of the country through developing and promoting the key strategic sectors of the economy. In this study, we employed most commonly used financial ratio tools on a sample of two (2) development financial institutions to evaluate their performances so as to indicate how well they are prepared to meet the socio-economic development objectives of the country. To the best of our knowledge, related study assessing the performance of DFIs in Malaysia is scant. Thus realizing from the scarcity of studies on this component of financial system particularly in the case of Malaysia, we consider the present effort to be worthy addition to the existing literature in this line. To achieve our objectives, we used data and other relevant information collected from the annual reports of individual Development Financial Institutions under consideration. In addition, we also utilized Annual Reports of Bank Negara Malaysia or Central Bank of Malaysia (BNM-AR). The results showed that the financial health of the two DFIs under this study is sound but comparatively Bank Rakyat (BR) is in better position than its peer Bank Simpanan Nasional (BSN). The sound financial health also indicates the potential ability to cater the financial needs of the strategic sector of the economy towards achieving the socio-economic development objectives of the country.